Global Research Trends on Peristomal Skin Complications in Ostomy Nursing Care: A Bibliometric Analysis - Sri Handayani; Yunita Sari (Indonesian Journal of Global Health Research, 2026)
Peristomal skin complications (PSCs) are common adverse outcomes following ostomy surgery and continue to challenge ostomy nursing practice. Despite extensive clinical discussion, a comprehensive understanding of global research trends, collaborations, and thematic development remains limited. This study examined the global research trend on PSCs in ostomy nursing care through a bibliometric approach, focusing on publication growth, collaborative networks, and key research themes. Publications indexed in Scopus and PubMed between 2006 and 2026 were retrieved using Publish or Perish with the keywords “peristomal skin complication”, “peristomal dermatitis”, “peristomal skin damage”, and “ostomy skin complication”. A total of 482 records were identified of which 146 English-language publications met the inclusion criteria after duplicate removal and title-abstract screening. Data were analyzed using VOSviewer (version 1.6.19) to generate co-authorship, keyword co-occurrence, and network visualizations with a minimum threshold of five occurrences. Publication output increased significantly after 2015, indicating growing scholarly interest. The Journal of Wound, Ostomy and Continence Nursing was the leading source, and the United States contributed the most publications. Four thematic clusters were identified: nursing roles, postoperative complications, determinants of PSCs, and ostomy technologies. These findings highlight research gaps and support future efforts to enhance early risk detection, prevention strategies, and evidence-based ostomy nursing care.